Determination of satellite parking locations and capacities in the University of the Philippines Diliman campus - Lim, Ernest Gabriel B.; Noble, Diane Clarisse N.; Regidor, Jose Regin F. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Satellite parking is an effective scheme that universities implement to resolve campus parking problems. This study aims to determine strategic locations for possible satellite parking in UP Diliman Campus in order to alleviate the current traffic volume situation and address the lack of parking spaces. The parking capacities of the satellite parking facilities were also computed. Different clusters were identified by subdividing the general areas within the campus. Data from an undergraduate study by Eserjose on the "Estimating Parking Supply and an Inventory of Parking Policies in UP Diliman" was taken and analyzed for the size estimation of possible satellite parking facilities. The acceptability of these proposed satellite parking spaces was determined through a perception survey which was conducted over the course of the semester. Boih the results from parking size estimation and acceptability survey of different colleges were taken into account in determining the strategic locations for satellite parking within the campus.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Campus parking; University of the Philippines -- Parking; Automobile parking